Why adopt transparency? The publication of central bank forecasts - Petra M. Geraats (European Central Bank (ECB), 2001)
Recently, several central banks have abandoned the usual secrecy in monetary policy and become very transparent. This paper provides an explanation for this puzzling fact, focussing on the disclosure of central bank forecasts. It shows that transparency reduces the inflationary bias and gives the central bank greater flexibility to respond to shocks in the economy. Furthermore, it makes it easier for a central bank to build reputation. To achieve these benefits of transparency it is generally necessary to publish the conditional central bank forecasts for both inflation and output.
Keywords: E52; E58; 330